CARACTERIZAÇÃO MORFOANATÔMICA, ESTUDO FITOQUÍMICO E AVALIAÇÃO DA CITOTOXICIDADE DE Euphorbia umbellata (Pax) Bruyns (EUPHORBIACEAE) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
Euphorbia umbellata (Pax) Bruyns, also known as janauba, belonging to the Euphorbiaceae family and it is the nomenclature accepts for Synadenium grantii Hook. f and Synadenium umbellatum Pax, which are synonymies according to some bibliographical references. It is popularly an employed species for the treatment of several cancer types, being the latex the vegetable part used for this purpose. In way to identify the species correctly, to contribute with the quality control and to correlate scientific studies of evaluation anticancer with the use etnopharmacologic, the proposed objectives were: to explore the morphoanatomy of E. umbellata; to evaluate the toxicity for the cells HeLa, HRT-18 and Jurkat and to proceed the phytochemistry investigation in the search of active substances. For the analysis macro and microscopic, leaves and stems of specimens designated as Synadenium grantii Hook. F (in Ponta Grossa) and Synadenium umbellatum Pax (in Goiânia) were previously fixed fastened in FAA solution. The material was sectioned by hand in the transverse and longitudinal directions. Astra blue and basic fuchsin were employed for staining. The citotoxicity of the latex was studied through biological rehearsals, with methodologies of mitochondrial reduction for MTT, internalization of VN for lysosomes; morphology for May Grunwald and Giemsa; membrane integrity for trypan blue; calculation of IC50; quantification of the content of DNA for DPA and propidium iodide; morphology for acridine orange and flow citometry. The phytochemistry, accomplished by accompaniment of biological rehearsals (biomonitored) results, it was done with the fraction Hex. The results ethnobotanical proved that the two specimens evaluated treat of the same plant which should be correctly denominated Euphorbia umbellata (Pax) Bruyns. These results elucidated the epicuticular wax, paracytic stomata and non-glandular trichomes; as well as laticifers; and they revealed chemical markers as the outstanding presence of the latex; composed lipophilic and phenolics compounds; starch and mucilage. The experimentation in vitro showed that the leukemic cells were firstly more responsive to the latex and later to the fraction Hex. IC50 calculated for the hexane fraction was of 1,87 μg/mL, value this that turns the composed phytocomplex of this fraction a promising antitumoral agents. After comparison with IC50 of non neolpasic cells, it was demonstrated IS of 5,98 and this corroborates the existence of selectivity action in relation to the analyzed cells. For flow citometry stop of cellular progression was verified, with substantial increase of the cells in phase G0/G1 and decrease of these in the phase G2/M. The phytochemistry study could contribute to the isolation of two identified triterpenes for techniques of nuclear magnetic resonance (RMN), being a pentacyclic denominated as germanicol acetate and for the first time isolated of this vegetable species and other tetracyclic designated euphol and already isolated of this Euphorbia umbellata (Pax) Bruyns.
Keywords: Janaúba; látex; câncer; linhagens tumorais; Janaúba; latex; cancer; tumoral lineages; CNPQ::CIENCIAS DA SAUDE::FARMACIA